Digital Marketing Business Strategy for Halal Products in Tangerang City: A Case Study of the Seblak Crackers MSME - Diana Dewi, Nur (SKeTsa Bisnis (e-jurnal), 2025)
Introduction; This study investigates factors influencing consumers intention to book hotels online using the Stimulus-Organism-Response (SOR) theory. The research is motivated by the growing trend of digital transformation in the hospitality industry, where user trust and convenience play crucial roles in shaping online booking behavior. Methods; A quantitative approach was employed by distributing online questionnaires to individuals who had previously booked hotels online, resulting in 448 valid responses being collected. Data were analyzed with validity and reliability tests, and hypothesis testing was conducted using the Structural Equation Modeling (SEM) technique. Respondents were selected through judgmental sampling to ensure relevance. Results; The findings indicate that perceived trust is the key variable exerting a significant direct influence on booking intention, an effect which is moderated by promotional offers. Notably, external stimuli such as online reviews, convenience quotient, and mobile application quality primarily influence booking intention indirectly, acting through their significant impact on perceived trust, which functions as a key mediator. Conclusion; The study concludes that strengthening users’ trust, satisfaction, and overall digital experience can enhance consumers’ willingness to engage in online hotel booking. These results offer practical insights for application developers and hotel managers to design trustworthy, user-friendly platforms and promotional strategies that align with changing consumer expectations.